'I AM SO ANGRY AND FRIGHTENED TO BE AT THIS STAGE OF MY LIFE': OBSERVATIONS OF GRIEF AND LOSS IN COMMUNITY ADVANCE CARE PLANNING GROUP EDUCATION. Issue 2 (1st June 2013) - Crowe, L; Boddy, J; Chenoweth, L
Abstract : Background: The ACP literature has a paucity of information in relation to the loss and grief experiences for people when contemplating engagement in ACP. Without this information engagement of certain populations and resolution of barriers to ACP may be difficult to overcome. Aim: To explore the incidence and themes of loss and grief that were shared within the context of ACP education workshops. Methods: A qualitative approach was used with participant observation and reflective journaling to record events within the implementation of ACP workshops. Thematic analysis was then employed to identify the various themes and frequency of loss and grief issues disclosed within the workshops. Results: There were two to three significant loss and grief statements made or disclosures of personal losses in each workshop. Loss and grief themes included fear of death, loneliness, suffering and vulnerability. Grief experiences included watching loved ones be palliated or die in a way that did not match personal values. Discussion: Loss and grief for older people outside the context of bereavement is under researched. Despite recognition of depression in the elderly there is scarcity in the literature of general grief and loss experiences and how this may impact the engagement and participation in ACP training. There are both historical and sociological grief and loss issues for this generation which require exploration for successful engagement in ACP planning. Conclusion: Participants had many fears related to previous loss experiences and misconceptions of the ACP process. Disclosures resulted in increased participation in the group and greater understanding of the benefits of the ACP process.